Insight Improvement of Residences on Disaster Risk Management in Kampung Muang, Samarinda: Pengayaan Wawasan Warga tentang Manajemen Risiko Bencana di Kampung Muang, Samarinda - Sari, Dharwati P; Utomo, Pandu K; Akhmad, Nuralam; Rizki Amelia Putri (ReTII, 2022)
Muang Ilir settlement is one of the areas in Samarinda that faces flooding during the rainy season. Most of the residents, whose education level is still relatifly low, causes inadequate knowledge of disaster risk management. This Community Service activity in Muang Village was carried out by identifying the level of community knowledge about flooding and disaster mitigation, followed by the delivery of basic knowledge of risk management in a humane manner and adapted to the ability of residents to capture new information. The activity ended by evaluating the residents’ insights in the form of questions. As a result, an increase in knowledge was obtained by the residents as evidenced by the ability to answer more questions than before being given new information/insight.